Development of hybrid fields — prospective trend of natural gas recovery - Lukin, A.E. (Reports of the National Academy of Sciences of Ukraine, 2018)
The XXI century should become the transition stage between the epoch of competing energy-carriers (coal, oil and oil products, gas, uranium, etc.) to the era of unexhaustible cheap ecologically nonpolluting energy sources (thermonuclear or hydrogen energetics?). Natural gas methane — with its unexhaustible resources — will be of crucial importance on this stage. However, it calls for increasing the volumes of the gas recovery that, in its turn, requires the cardinal increasing of the efficiency of prospecting-exploratory works and new methods of fields development. Specifically great prospects ought to be connected with hybrid fields that combine traditional and non-traditional (tight reservoir gas) gas resources. Many different types of oil, gas-condensate, gas, and heterophase fields (pools) fall in this category. So, the ideology and methodology of development of such fields should be radically altered. This is of special significance for Ukraine, whose gas potential is much higher as compared with oil.